1983
DOI: 10.1126/science.221.4611.649
|View full text |Cite
|
Sign up to set email alerts
|

Confirmation of the Carolina Slate Belt as an Exotic Terrane

Abstract: An assemblage of Middle Cambrian Atlantic faunal province trilobites has been found in the rocks of the Carolina slate belt near Batesburg, South Carolina. Geologic and paleomagnetic data suggest that the Carolina slate belt and the adjacent Charlotte belt constitute an exotic terrane that was accreted to North America in early to middle Paleozoic time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
50
0

Year Published

1990
1990
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(52 citation statements)
references
References 22 publications
2
50
0
Order By: Relevance
“…The former is represented by two species of the Amecephalina (Harrington and Kay, 1951;Rushton, 1962;Borello, 1971;Forero-Suárez, 1990) or Balthyuriscus-Elrathina Zones (Borello, 1971) from the Precordillera of northwestern Argentina. The latter, an Acado-Baltic trilobite, can be found within the Carolina Slate belt (Secor et al, 1993), in the Paradoxides zone of eastern New England (Devine, 1985), eastern New Foundland, New Brunswick and Avalon Peninsula (North, 1971;Palmer, 1973). Recent reviews point out that the Cambrian fauna reported from Colombia is typical 'Atlantic Realm' affinity (Benedetto, 2004).…”
Section: Constraints On the Relative Position Of Nw South America Fromentioning
confidence: 98%
“…The former is represented by two species of the Amecephalina (Harrington and Kay, 1951;Rushton, 1962;Borello, 1971;Forero-Suárez, 1990) or Balthyuriscus-Elrathina Zones (Borello, 1971) from the Precordillera of northwestern Argentina. The latter, an Acado-Baltic trilobite, can be found within the Carolina Slate belt (Secor et al, 1993), in the Paradoxides zone of eastern New England (Devine, 1985), eastern New Foundland, New Brunswick and Avalon Peninsula (North, 1971;Palmer, 1973). Recent reviews point out that the Cambrian fauna reported from Colombia is typical 'Atlantic Realm' affinity (Benedetto, 2004).…”
Section: Constraints On the Relative Position Of Nw South America Fromentioning
confidence: 98%
“…In South Carolina, this sequence is divided into the Rlchtex (>3. 3 "km[2.0 mi]) and the Asbill Pond (>5 km [3.0 mi]) Formations (Secor et al 1983;Secor et al 198G Secor and Wagener 1968;Secor 1987). Structural relationships indicate that the @chtex Formation overlies the Persimmon Fork Formation, although it is uncertain if the contact is stratigraphic or tectonic (Secor 1987).…”
Section: ')mentioning
confidence: 99%
“…1982 Hills andButler and Fullagar 1975;Wright and Seiders 198Q LeHuray 1987). The Richtex and Asbill Pond formations were deposited during the Middle Cambrian (525 Ma), based on occurrences of sponge spicules and Acado-Bak.ic trilobites (Paradoxides) (Secor et al 1983;Bourland and Rigby 1982).…”
Section: ')mentioning
confidence: 99%
“…Two types of basements are possible, Grenville or Gondwanan. Although neither basement is exposed in South Carolina (Secor et al, 1983), in the following section we generally assess the contributions of the nearest basements to the gold deposits.…”
Section: Paleozoic Evolutionmentioning
confidence: 99%
“…The slate belt extends from Georgia to Virginia and is part of the Carolina terrane ( Fig. 1), which constitutes a portion of the Carolina zone (e.g., Secor et al, 1983;Horton et al, 1989 recorded as early as the 1820s at the Haile and Brewer mines (Worthington, 1993). The gold deposits in the slate belt remained in production until the 1990s.…”
mentioning
confidence: 99%